Descemet Membrane Endothelial Keratoplasty With a Pull-Through Insertion Device: Surgical Technique, Endothelial Cell Loss, and Early Clinical Results. Issue 5 (May 2020) - Tan, Tien-En; Devarajan, Kavya; Seah, Xin-Yi; Lin, Shu-Jun; Peh, Gary Swee Lim; Cajucom-Uy, Howard Yu; Ang, Marcus; Mehta, Jodhbir Singh; Tan, Donald Tiang Hwee
Abstract : Purpose: To describe a surgical technique for Descemet membrane endothelial keratoplasty (DMEK) using a pull-through, endothelium-in insertion device, the DMEK EndoGlide. We evaluated the endothelial cell loss (ECL) associated with the EndoGlide-DMEK (E-DMEK) technique in both ex vivo and prospective clinical studies. Methods: The ex vivo study involved calcein acetoxymethyl staining and preparation of DMEK grafts, which were trifolded endothelium-in, loaded into the EndoGlide, pulled through, and unfolded in imaging dishes. Inverted fluorescent microscopy was performed, and ECL was quantified using trainable segmentation software. The prospective clinical series describes the outcomes of consecutive surgeries using the E-DMEK technique. Grafts were pulled through the EndoGlide with forceps and unfolded in the anterior chamber endothelium-down. Our main outcome measure was ECL in both studies. Results: In the ex vivo study with 9 human donor corneas, mean ECL was 15.2% ± 5.4% (n = 9). In our clinical series of 69 eyes, leading indications for surgery were pseudophakic/aphakic bullous keratopathy (47.8%), previous failed grafts (23.2%), and Fuchs endothelial dystrophy (18.8%). Rebubbling and primary graft failure rates related to E-DMEK were 11.6% and 1.5%, respectively. Among eyes with at least 6 months of follow-up, mean preoperative endothelial cell density was 2772 (range 2457–3448) cells/mm 2, and postoperative endothelial cell density was 1830 (range 541–2545) cells/mm 2 . Mean ECL was 33.6% (range 7.5–80.4; n = 32) at the 7.1 (range 6–11) months follow-up. Conclusions: The ex vivo and pilot clinical studies suggest that E-DMEK shows acceptable rates of ECL, with safe and promising early clinical outcomes. Abstract : Supplemental Digital Content is Available in the Text.